The Russian labor market in the context of the digitalization - Sadovnikova, Natalia; Babich, Svetlana; Lebedinskaya, Olga (Nexo Revista Científica, 2022)
To ensure the competitiveness of the Russian economy in the international arena, it is necessary to increase labor productivity. However, its indicators lag significantly behind similar indicators in economically developed countries. The necessary conditions for the growth of labor productivity in the regions of the country are the technological re-equipment and modernization of production, the development and implementation of modern advanced information technologies in all areas, the presence of a highly professional workforce with the necessary competencies in the context of the digitalization of the economy.